The Effectiveness of E-Comic Media Based on Scientific Literacy for Teaching Single and Mixed Substance Materials - Damayanti, Laila; Wulandari, Desi; Busyairi, Ahmad; Wadiyo, Wadiyo; Raharjo, Tri Joko; Sumartiningsih, Sri (Universitas Negeri Semarang, 2024)
This study aims to assess the effectiveness of scientific literacy-based e-comic media in improving students' learning outcomes related to the topic of single substances and mixtures. A quasi-experimental design with a pretest-posttest approach was employed, where the same group of 25 students from class VA at SDN Sampangan 02 and class VB at SD Lab School UNNES were tested before and after using the e-comic media. The e-comic was designed to engage students and enhance their understanding of scientific concepts through interactive narratives and visual illustrations.The study found that the use of e-comic media significantly improved students' learning outcomes, as indicated by the results of a paired t-test (t = 9.766, p < 0.05) and N-gain analysis, which showed a medium level of improvement (N-gain = 0.584). Teacher and student responses were overwhelmingly positive, with 93% and 95% satisfaction rates, respectively. This suggests that e-comic media is an effective tool for improving students' scientific literacy and understanding of the material. The findings support the use of digital media in science education, particularly for engaging students in complex scientific concepts.